I-Magelang as an Implementation of Information Technology-Based Magelang Library Service Innovation to Improve Public Literacy Access at the Library and Archives Service of Magelang City, Central Java - Leny Adriana Mesah; Purbudi Wahyuni; Raden Heru Kristanto (UPN Veteran Yogyakarta, 2022)
This study aims to find out a relatively comprehensive picture of the implementation of iMagelang innovation as a means in an effort to increase access to community literacy, identify obstacles in the implementation of iMagelang innovation and obtain suggestions and recommendations for theoretical and practical interests from research. Data analysis methods include interactive models and qualitative descriptive analysis. The results of this research iMagelang is an institutional, not personal innovation, whose existence can be sustainable and has the potential to be developed because of the ecosystem / innovation environment that supports continuity of implementation. In its implementation, iMagelang has felt the benefits for the community but still contributes little in increasing the number of library service visits, which means it is also relatively small in increasing access to community literacy. Limited public ownership of devices and networks for iMagelang access, Lack of understanding level of user community, lack of number and type of literacy collections and lack of socialization are factors causing the low contribution of iMagelang implementation in improving access to community literacy. Socialization is a potential factor that the Magelang City Public Library can do to increase iMagelang access, although it still needs further research at the level its effectiveness.